2019
DOI: 10.1002/mar.21213
|View full text |Cite
|
Sign up to set email alerts
|

“It's MY Service, it's MY Music”: The role of psychological ownership in music streaming consumption

Abstract: Music streaming services have become today's most popular way of consuming music. These services give their users access to a comprehensive music library without providing legal ownership of that music. However, recent research suggests that music streaming users still continue to experience feelings of ownership. To advance our understanding, this study investigates the role of psychological ownership in music streaming consumption. In particular, based on the theory of psychological ownership, it is analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 72 publications
(186 reference statements)
5
40
0
Order By: Relevance
“…CUST is an essential element and can provide usability, convenience, and improved performance (S. Kim et al, 2016). The gaming environment's CUST aspect can provide personalization to the end‐user and positively affect consumers' purchase intentions (Danckwerts & Kenning, 2019; Wottrich et al, 2017). The CUST function in an AI‐powered avatar can help gamers to use different in‐game features during gameplay.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…CUST is an essential element and can provide usability, convenience, and improved performance (S. Kim et al, 2016). The gaming environment's CUST aspect can provide personalization to the end‐user and positively affect consumers' purchase intentions (Danckwerts & Kenning, 2019; Wottrich et al, 2017). The CUST function in an AI‐powered avatar can help gamers to use different in‐game features during gameplay.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Mifsud, Cases, and N'goala (2015) conceptually specify service appropriation as "a process by which customers make the service their own" (p. 719) and develop possessive feelings, over time and through their investment of personal resources. Sinclair and Tinson (2017) and Danckwerts and Kenning (2019) identify psychological ownership in consumers' experiences of music streaming; Karahanna et al's (2015) study also reveals that psychological ownership needs motivate social media consumption. Consumers also refer to their meaningful relationships with virtual consumer goods, such as in-game avatars (Watkins, Denegri-Knott, and Molesworth 2016) or holograms (Carrozzi et al 2019).…”
Section: Extended Self Theory and Psychological Ownershipmentioning
confidence: 99%
“…Prior research suggests that the importance consumers assign to owning material objects constitutes a critical barrier to ABS use (Kahneman, Knetsch, and Thaler 1990; Richins 2004; Weiss and Johar 2013); the importance of material possessions for consumers relates negatively to their use of ABS (Bardhi and Eckhardt 2012; Belk 2014). However, feelings of perceived ownership can emerge toward a range of material and immaterial objects such as cars, music streaming, and even augmented reality holograms (Carrozzi et al 2019; Danckwerts and Kenning 2019; Pierce, Kostova, and Dirks 2003). We thus leverage symbolic self-completion theory (Wicklund and Gollwitzer 1982) to propose that psychological ownership of ABS might satisfy consumers’ need for ownership and substitute for material ownership.…”
mentioning
confidence: 99%
“…Zhao, Chen and Wang [3] revealed that the perceived control of users in the context of social media (e.g., LINE) has a positive effect on psychological ownership and consequently leads to continued usage and willingness to pay more. Moreover, Danckwerts and Kenning [18] stated that, in online streaming, users' perceived control is positively related to music-based psychological ownership. Second, getting to know the target intimately means that an individual has to relate to his/her possessions by getting to know the object and feeling intimacy toward it.…”
Section: Psychological Ownership In the Online Contextmentioning
confidence: 99%
“…offer innovative tools, applications, and games in addition to their basic function of sharing information with others, thereby increasing user interaction and connection frequency [3]. In other words, the interaction between a user and a service, and the user's deeper involvement in the service refers to becoming familiar with the service [18,19], which leads to a higher psychological ownership of the service. Finally, investing the self in the target refers to an individual investing money, time, energy, effort, and attention into an intangible/tangible target.…”
Section: Psychological Ownership In the Online Contextmentioning
confidence: 99%